Advanced Morphological Technique for Automatic Brain Tumor Detection and Evaluation of Statistical Parameters. (2016) - Sudharani, K.; Sarma, T.C.; Prasad, K. Satya
Abstract: A tumor is uncontrolled growth of the abnormal tissue in the body. If this phenomenon is in brain is brain tumor. A tumor may lead to cancer. Image processing techniques are applied to magnetic resonance (MR) images to detect tumor and edema. The main objective of this paper is to present the automatic segmentation method which separates non-enhancing brain tumors from healthy tissues in MR images by locating tumor position in the brain and to give complete statistical analysis of the tumor. By applying the algorithm presented in this paper we can determine the area of the tumor in the brain along with the area length in the vertical and horizontal planes, sensitivity of the tumor, specificity, similarity index can also be find. The knowledge of this information regarding tumor in the brain is important for diagnosis, planning, and treatment. The proposed algorithm can also be applied to the ground truth images. With the proposed algorithm the tumor detection and localization system was found to be able to accurately detect and localize brain tumor and processing time is less. This will help the physicians in analysing the brain tumors accurately and efficiently.